HIMMIA Qaulan Layyina Islamic Communication Ethical Principles (Akbar Islamic Youth Association) in Building Ukhuwah Islamiyah in Medan Helvetia District - Rubino; Muhammad Farisi (Sean Institute, 2022)
This study aims to determine HIMMIA's Qaulan Layyina Islamic Communication Ethics in Building Ukhuwah Islamiyah in Medan Hevetia District. The method used in this research is a qualitative method. Because this research explains the phenomena that occur in the field by collecting data obtained from research informants by conducting observations, interviews and documentation. The approach used is the approach of communication science (Islamic Communication). The results of the research found by researchers are as follows, when the communication process occurs, Islamic communication ethics HIMMIA uses is the principle of qaulan layyina communication With that gentleness there will be a communication that will have an impact on the absorption of the contents of the speech by the person being spoken to so that there will not only be the arrival of information but will also change the views, attitudes and behavior of the person being invited talk. So that from the data that researchers got, Islamic Communication Ethics has been well implemented and created good interpersonal relationships so that it can increase Islamic ukhuwah in Medan Helvetia District. Increasing ukhuwah Islamiyah is manifested in the form of mutual cooperation, cooperation in completing work, helping each other when someone needs help, respecting each other, forgiving each other, caring for others.